Aqueous Lubrication: A Self‐Assembled Binary Protein Model Explains High‐Performance Salivary Lubrication from Macro to Nanoscale (Adv. Mater. Interfaces 1/2020). Issue 1 (10th January 2020) - Xu, Feng; Liamas, Evangelos; Bryant, Michael; Adedeji, Abimbola Feyisara; Andablo‐Reyes, Efren; Castronovo, Matteo; Ettelaie, Rammile; Charpentier, Thibaut V. J.; Sarkar, Anwesha
Abstract : Salivary pellicle is an outstanding bio‐lubricant that coats and protects our tongue, teeth and oral mucosa. Supported by sophisticated multi‐scale tribological analyses and real‐time adsorption techniques coupled with self‐consistent field theory calculations, Anwesha Sarkar and co‐workers demonstrate in article number 1901549 for the first time that the unique lubrication performance of salivary pellicle is a result of electrostatic self‐assembly between hydrated mucin proteins and positively‐charged protein, latter acting as a 'molecular glue' between the mucin‐mucin and mucin‐surface.